Efeitos das combinações de prática constante - variada na aprendizagem da habilidade motora saque do voleibol - Cintia de Oliveira Matos (2017)
The studies about practice schedule show that combining practice schedules improves the learning of both generalized motor program (GMP) and parameters of a motor skill. In general, these studies combined constant and random practices. However, few studies tested this question with complex tasks and other variable practice schedules, futher the results are ambiguous about the learning of both aspects of the skill (i.e., PMG and parameters). The purpose of this study was to investigate the effects of different variable practices, performed after the constant practice, on the learning of both GMP and parameters. This question was investigated with a sample of 44 volunteers aged between 12 and 14 years old, self-declared right-handers, without experience in the task. The participants should perform the volleyball tennis serve aiming to reach the target bulls-eye positioned on the floor on the opposite side of the court. All the volunteers performed a pretest whose score was adopted to counterbalance them into four groups: one that combined the constant and blocked practices (CBG), one that combined the constant and serial practices (CSG), one that combined the constant and random practices (CRG) and another that performed only the constant practice (CG). During the acquisition phase, the participants performed 252 serves divided into 6 sessions. In the first half of acquisiton phase, all groups performed the serves from only one position of the court. In the second half, excepted to the constant practice group, the task was performed from three different positions. The retention test was performed 72 hours after finished the acquisition phase. Data analyzes were run in relation to the movement pattern (PMG) and in relation to the score (parameters of the skill). The acquisition phase intra-group analysis was carried out with the Students t-test and the retention test inter groups analysis was carried out with a one-way ANOVA.The results showed that CBG, CSG and CRG improved the GMP. Moreover, the detailed analysis of movement pattern showed that these same groups improved the ball throwing component. In relation to PMG consistency, it was found improvement to groups that combined the constant and blocked practices and constant and random practices. In the parameters measure was identificated improvement only to constant group. In conclusion, none combination of practice led to learning of both aspects. It is possible that during the learning of complex tasks the modifications from practice variation increase cognitive demand in relation to movement pattern to that the task can be performed. On the other hand, the constant practice makes possible to improves attention demand on parameters adjustment.